The use of Gestalt Psychology in Project Work - Glushchenko, Valery Vladimirovich (ASEAN Journal of Educational Research and Technology, 2023)
The work aims to increase the effectiveness of innovative projects using tools based on the use of Gestalt psychology. The methodology of Gestalt psychology in its structure, conceptual apparatus, and properties is more suitable (than traditional psychology) for project activities. Therefore, Gestalt psychology can be effectively applied in project activities, and therefore Gestalt psychology has prospects for development in the field of project activities.